30 The Role of A Virtual Clinic in Reducing Waiting Times for Out-Patient Follow-Up. (6th February 2020) - Thomson, F; Richards, K
Abstract: Topic: Hospital admissions for older people are increasing with subsequent pressure on out-patient (OP) clinics. By early 2018, 350 patients were waiting up to 6 months for follow-up, with limited capacity in existing clinics. There were concerns regarding potential harm to patients from delayed review of significant results. Intervention: A working group considered options for managing the OP waiting list. We decided to pilot a fortnightly virtual clinic (VC) where cases were reviewed without the patient present. All patients awaiting results were listed for the VC rather than routine OP. Each VC had 50 patients listed. Patient's GP received a clear action plan. Clinic rules were modified as issues were identified. Links with other specialities evolved reducing the number of missing results. Data was analysed for 50% of consultations between January 2018 and March 2019. Improvement: 311 VC appointments were reviewed: 207 in 2018 and 104 up to March 2019. Maximum 25 cases could be completed per clinic, additional sessions cleared initial backlog within 3 months. Completion time/case ranged from 2-15 minutes depending on complexity. Main reason for VC was test results: 82% in 2018, increasing to 93% in 2019. 61% in 2018, 80% in 2019 were discharged directly from VC. 20% required a 2nd VC for outstanding results. OP review post-VC fell from 16% in 2018 to just 2% in 2019. General OP requirements fell from 24hrs to 10 hours/ week as a result of VCs, releasing consultants for other clinical areas. Discussion: VCs are an effective means of reviewing outstanding results from recent admissions and OP consultations. Routine listing of patients with outstanding investigations provides a safety net. Most results are normal and do not require follow-up. Repeat CXRs at 6 weeks continue to be requested for severely frail people who are unlikely to benefit.